How do residents assess the social impact of tourism? - Milošević, Srđan; Perić, Dušan; Škrbić, Iva (Hotel and Tourism Management, 2021)
Tourism plays an important role in the economic and cultural development of society, producing many positive and negative effects. This study aimed to (a) assess the impact of tourism on modern life in Montenegro based on the attitudes of residents and (b) standardize instrument (questionnaire) for assessing these impacts. The sample formed by 521 adults from three different tourist regions (coastal, continental, mountainous). The questionnaire has high validity and reliability. Two components (two independent scales) have been extracted – the negative and positive social impact of tourism. It was found that the increase in positive impacts is followed by an increase in negative effects too. Type of the region, level of municipal development and engagement of respondents in tourism influence significantly the differences between attitudes of examinees. Those who live by tourism most respect its importance for local development.